Total knee arthroplasty revision risks depending on the bone cement used—Data from 50,545 knee replacements of the Catalan Arthroplasty Registry - Daniel Perez‐Prieto; Katharina Koetter; Albert Fontanellas‐Fes; Olga Martínez‐Cruz; the RACat working group (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose Clinical data on individual bone cement brands and viscosities in cemented total knee arthroplasty (TKA) is scarce. The Catalan arthroplasty registry (RACat) documents usage of cement brands including viscosities and the inclusion of antibiotics. The objective was to compare the clinical performance of the widely used bone cement brand PALACOS® to other blinded bone cement brands in TKA using data from the RACat. Methods Patient data on 50,545 primary TKA between 2007 and 2017 in the RACat were analysed retrospectively. Implant survival of PALACOS bone cement was compared to other blinded bone cement brand groups using the all‐cause revision risk as primary study endpoint. Results Comparing implant survival, it was found that (1) PALACOS® (with or without gentamicin) was associated with a significantly lower revision risk compared to other cement brands (with or without antibiotics) (p = 0.001): RR PALACOS 2.03% versus RR other brands 3.88%, and RR PALACOS+G 1.84% versus RR other antibiotic‐loaded bone cements (ALBC) 3.85%; (2) ALBC (all brands) did not reduce the risk of revisions (p = n.s) compared to plain bone cements (PBC); and (3) the medium viscosity PALACOS MV+G showed the lowest reoperation risk versus other ALBC (all viscosities): RR 1.12% versus RR 3.85%. Competing‐risk regression models confirmed reduction in revision risk for all PALACOS compared with other brands (p = 0.001) and for PALACOS+G compared with other ALBC (p < 0.001) but showed no difference when comparing all ALBC with all PBC (p = 0.403). Comparing PALACOS MV+G with all other ALBC showed reduction of revision risk (p < 0.001) and no difference when comparing PALACOS medium viscosity (MV) with all other PBC (p = 0.108). Conclusions Type of cement brand, viscosity and the addition of antibiotics have an impact on revision risk of TKA. Medium viscosity cement with gentamicin (PALACOS MV+G), for which no clinical data were previously available, was associated with the lowest revision risk in TKA. Level of Evidence Level III, retrospective comparative study.